Interactive Course Registration System with Visualized Timetable (International Journal of Innovative Computing, 2024)
Course Registration System (CRS) is a web-based application that can be accessed by any platform and device as long as there is the internet that can be connected to the web service. The target user of the system is the student and staff of the school of computing Universiti Teknologi Malaysia (UTM), Johor Bahru. The CRS is a system that can provide a feature that helps the student to perform the course registration process sufficiently. The CRS system is developed through a hybrid agile waterfall methodology. The hybrid methodology provide systematic documentation for the project while offer flexibility during its development phase. A visual timetable generated and able to view the list of course mate in the registration process are major features that CRS provide. These features are the basic things that should be able to be implemented in course registration for it easier for the student to identify the clash course taken and make their study plan. At the end the CRS system able to provide a complete feature that make students register for a course with less burden and less complexity through the visualized table feature.
Keywords: Web-Based Application, Online Enrollment System, Hybrid Agile Waterfall Methodology